An Improved Synchronization Scheme for Non-Integer Multiple Spread Spectrum. (February 2019) - Miao, Gumin; Feng, Man; Xu, Liang
Abstract: Non-integer multiple spread spectrum systems are gradually being widely used in civil and military communications due to their superior communication security and signal privacy. For the difficulties in the capture of pseudo-codes in the non-integer multiple DSSS-DQPSK system under the large Doppler shift, a fourth power PMF-FFT (4th-Power-PMF-FFT) scheme is proposed. The system is optimized by zero-padding and batch FFT algorithms to eliminate scallop loss, improve carrier frequency estimation accuracy, and reduce hardware resource consumption The simulation results proved the effectiveness of the method.